ENVIRONMENTAL MIGRANTS-REFUGEES AND CRISIS MANAGEMENT POLICIES (PANGEEA, 2025)
Climate change is one of the biggest emerging environmental challenges of our time, which is taking on ever greater dimensions from the time of the industrial revolution to today, with incalculable adverse effects on the economy, physical and mental health, and society in general. The effects of climate change force many people every day to seek shelter in other parts of the world. According to many scientists, climate migration is the most important problem that humanity will face in the coming decades. Although objections have raised from time to time about the reliability of estimates of climate displacement, no one can dispute the existence of the phenomenon and the consequent trend of population displacement. Additionally, environmental migration can be the result of a slow process of environmental degradation. The international community will be asked to face significant challenges regarding this issue and it will become imperative to create a comprehensive proposal, which will act as a shield of protection and which will aim to defend the rights of people who are forced into displacement due to environmental degradation. Finally, the research part presents the research conducted and analyzes the conclusions obtained from the collection and analysis of the questionnaire data, which includes targeted questions of a mixed type and which was distributed to people in the population who were easily accessible (convenience sampling), so as to ensure on the one hand the greatest possible participation of them in this research and on the other hand to illuminate as fully as possible the prevailing opinions and beliefs of these individuals regarding the issue under consideration.
Keywords: environmental migrants-refugees; climate change; managing policies